A model and method for solving a dynamic transport problem - Davulis, Gediminas (Journal of Business Economics and Management, 2004)
The problem of optimal development of transport network is considered. We have to define a plan of network development, i.e. a network state at fixed time moments possible the scope of allocated resources such that the total expenses for reconstruction of the network and construction of its new elements as well as for passenger and cargo transportation be the lowest. Thus the problem considered can be described by the optimization model with a non‐linear non‐convex objective function and linear constraints of special structures. Since that is a non‐convex problem with a lot of extreme therefore one can expect to find only an approximate solution, close to a global one, at best. There is no effective and universal solution methods for this problem even in the sense of a local solution. This paper discusses a method for solving the problem using the synthesis of static section, that allows us to decompose dynamic problem into the set of static problems of a smaller volume, and contour optimization methods. The experimental calculation confirm that the proposed method is suitable for solving problem represented in the paper. First Published Online: 14 Oct 2010